Thermal aware task sequencing on embedded processors - Sushu Zhang; Chatha, Karam S (Design Automation Conference, 2010)
We seek to maximize the throughput of a periodic application by obtaining an optimized task sequence and dynamic voltage/frequency scaling schedules subject to a peak temperature constraint. We first derive an optimal initial temperature that can generate optimum solutions. We next present optimal solutions for several subproblems. Finally, we propose novel algorithms for the general instances of the problem. Experimental results show that our techniques out perform existing approaches in both design quality and solution times.